Dextranomer/Hyaluronic Acid Copolymer (Dx/HA) Has no Effect on Bacterial Growth in Culture Media With or Without Antibiotic Discs - R, Karabulut; F, Doğruman-Al; Z, Türkyılmaz; K, Sönmez; F, Demirel; N, Sultan; AC, Başaklar (IIUM Medical Journal Malaysia, 2010)
Introduction: Endoscopic treatment of vesicoureteral refl ux (VUR) by subureteral injection of biocompatible polymers is an established treatment option for refl ux. Dextranomer/hyaluronic acid copolymer(Dx/HA) has gained wide popularity for treating VUR. We decided to investigate the antibacterial activity of Dx/HA and its interaction with antibiotics in in-vitro conditions. Materials and Methods: Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Proteus mirabilis suspensions were inoculated into Mueller-Hinton agar media and 30 μl of Dx/HA was inoculated in 5 mm diameter pits and the plates were incubated at 37°C for 24 hours. At the end of the incubation period, inhibition zones around the discs were measured. Expansion of the inhibition zones towards the pits which contained Dx/HA was considered as synergism. Dx/ HA was inoculated into pits made in Mueller-Hinton agar medium without antibiotic discs but containing suspensions of bacteria. These media were incubated under the same circumstances and same measurements were done. All experimental procedures were performed twice. Increase in bacterial zone diameters for ≥ 5 mm was inoculated was regarded as signifi cant for each agent. Results: Dx/HA caused no difference in bacterial growth either with or without antibiotic discs as determined by inhibition zones in the culture media. Conclusion : Dx/ha will not contribute to UTI if it is used for the treatment of VUR in cases either with or without infection.